Robert Noonan's (Tressell's) membership card for Transvaal Executive Committee of the Centennial of 1798 Association (1898)
1898 "Robert Noonan's (Tressell's) membership card for Transvaal Executive Committee of the Centennial of 1798 Association" [t0606.jpg], 1898 Between about 1890-1899 Robert Noonan lived in South Africa. In 1898 he became a member of the Executive Committee of the Transvaal '98 Commemoration Committee, established to arrange a celebration of the centenary of the Irish uprising.